FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Kasus pada Kantor Pelayanan Pajak Pratama Semarang Barat) (Students' Journal of Accounting and Banking, 2012)
The purpose of this study was to examine and analyze the influence of perceptions of sanctions taxation of taxpayers, tax officials, taxpayers criteria compliant, taxpayer awareness and knowledge of taxation on taxpayer compliance.The population in this study is an effective individual taxpayers registered at the KPP Semarang Barat in 2010 as many as 2906. With population size (N) of 2906 and the percent leeway inaccuracy because the sampling error can be tolerated or chill (e) 0.1 of this study using 100 samples. The determination of an individual taxpayer which will be selected is to use simple random sampling technique. Methods of data analysis used were multiple linear regression analysis.The results of this study can be concluded that: (1) Perceptions of sanctions taxation compliance reporting a positive effect on individual taxpayers. (2) Perceptions of the council tax compliance reporting a positive effect on individual taxpayers. (3) Perceptions of the criteria required to obey a positive effect on tax compliance reporting individual taxpayer. (4) Awareness of taxpayer compliance reporting a positive effect on individual taxpayers. (5) Knowledge of tax compliance reporting a positive effect on individual taxpayers.Keywords: perception of the taxpayer's tax penalties, tax officials, taxpayers criteria compliant, taxpayer awareness, knowledge of taxation and taxpayer compliance